2017
DOI: 10.4314/jasem.v21i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aero-radiometric Data of Southern Anambra Basin for the Prospect of Radiogenic Heat Production

Abstract: High-resolution aero-radiometric data from three radio-elements (Uranium, Potassium and Thorium) were used and processed independently to investigate the Southern Anambra basin for the prospect of producing radiogenic heat. The rock types in the study area were outlined while processing the elements in each rock to evaluate the radiogenic heat production values. The results of the analysis of the radiogenic heat production of the study area ranges between 0.01 -5.43 µWm -3 . The highest heat produced came from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…On the radiometric survey, Kuforijimi and Christopher [25] carried out an assessment of Aero-radiometric data of Southern Anambra Basin for the prospect of Radiogenic Heat Production.…”
Section: Previous Work On Magnetic and Radiometric Methods Of Geophysical Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…On the radiometric survey, Kuforijimi and Christopher [25] carried out an assessment of Aero-radiometric data of Southern Anambra Basin for the prospect of Radiogenic Heat Production.…”
Section: Previous Work On Magnetic and Radiometric Methods Of Geophysical Surveymentioning
confidence: 99%
“…Kuforijimi and Christopher [25] correlated and mapped geothermal and radioactive heat production from the Anambra Basin, Nigeria. They studied area of latitudes 6°00'N and 7°30'N and longitudes 6°30'E and 9°00'E.…”
Section: Previous Work On Combined Magnetic and Radiometric Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in an aeroradiometric study carried-out by Adunu et al (2022) on Makurdi, Gboko, Kastina-Ala and Akwana areas to delineate prominent radiometric anomalies for solid minerals, it was revealed that the highest radiometric mineralization area were identi ed as Katsina-Ala and Akwana. Assessment of Aero-radiometric data of Southern Anambra Basin for the prospect of radiogenic heat production by Kuforijimi and Christopher (2017), concludes that high concentration of uranium, potassium and thorium in Aimeke and Ogobia shows high potentiality for geothermal energy and radiogenic heat production. These areas should be exploited for geothermal energy.…”
Section: Introductionmentioning
confidence: 99%